Use of Monoclonal Antibodies for the Identification of Leishmania spp. Isolated from Humans and Wild Rodents in the State of Campeche, Mexico - Silvia B CantoLara; Nicole R Van Wynsberghe; Alberto Vargas-González; Fanny F Ojeda-Farfán; Fernando J Andrade-Narváez (Memorias do Instituto Oswaldo Cruz, 1999)
The genus Leishmania includes 30 described species which infect a wide variety of mammalian hosts. The precise identification of leishmanial parasites at the species level is very important in order to determine whether an organism, causing the disease in a given area, is of the same biotype as that found in suspected mammalian reservoirs. The objectives of the present study were (1) to identify leishmanial parasites isolated from humans and wild rodents from the State of Campeche, an endemic focus of localized cutaneous leishmaniasis (LCL) in southern Mexico, using an indirect immunofluorescent assay (IFA) with monoclonal antibodies (Mabs); and (2) to determine if the parasites of the two types of hosts were of the same biotype. All the wild rodents (six Ototylomys phyllotis, eight Oryzomys melanotis, five Peromyscus yucatanicus and two Sigmodon hispidus) and 96% (24/25) of the human isolates were identified as Leishmania (L.) mexicana confirming that this specific LCL focus is a wild zoonosis. The presence of one human isolate of L. (Viannia) braziliensis in the State of Campeche, confirmed the importance of an accurate taxonomic identification at species level.